The unidimensionality and overestimation of metacognitive awareness in children:validating the CATOM - Ferreira, Paula da Costa; Veiga Simão, Ana Margarida; Lopes da Silva, Adelina (Anales de Psicología / Annals of Psychology, 2015)
Children often have difficulty in reporting their metacognitive functioning, which leads them to frequently overrating themselves under learning situations. Hence, this study presents a preliminary approach of how children’s awareness of their own metacognitive knowledge (MK) and metacognitive skills (MS) can be measured. Essentially, this study aims to understand how children (n =1029) report their metacognitive functioning. In a first analysis, PCA revealed an initial two-factor structure of the instrument (MK and MS). Item Response Theory was then used to analyse the unidimensionality of each dimension and the interactions between participants and items. Results revealed good item reliability for MK (.93) and MS (.80), and an average person reliability (.67) for MK and MS (.78) with good Cronbach’s α for MK (.84) and MS (.91). These results show the potential of the instrument, as well as a tendency of children to overrate their metacognitive functioning. Implications for researchers and practitioners are discussed.